2018
DOI: 10.1371/journal.pgen.1007839
|View full text |Cite
|
Sign up to set email alerts
|

RSM1, an Arabidopsis MYB protein, interacts with HY5/HYH to modulate seed germination and seedling development in response to abscisic acid and salinity

Abstract: MYB transcription factors are involved in many biological processes, including metabolism, development and responses to biotic and abiotic stresses. RADIALIS-LIKE SANT/MYB 1 (RSM1) belongs to a MYB-related subfamily, and previous transcriptome analysis suggests that RSM1 may play roles in plant development, stress responses and plant hormone signaling. However, the molecular mechanisms of RSM1 action in response to abiotic stresses remain obscure. We show that down-regulation or up-regulation of RSM1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 68 publications
1
55
0
Order By: Relevance
“…The tcp3 tcp4 tcp10, tcp3 tcp4 tcp5 tcp10, and tcp3 tcp4 tcp5 tcp10 tcp13 seeds were kindly provided by Tomotsugu Koyama (Kyoto University;Koyama et al, 2010). The hy5 hyh seeds were kindly provided by Liumin Fan (Peking University; Yang et al, 2018).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The tcp3 tcp4 tcp10, tcp3 tcp4 tcp5 tcp10, and tcp3 tcp4 tcp5 tcp10 tcp13 seeds were kindly provided by Tomotsugu Koyama (Kyoto University;Koyama et al, 2010). The hy5 hyh seeds were kindly provided by Liumin Fan (Peking University; Yang et al, 2018).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Previous studies showed that MYB TFs are involved in various biotic and abiotic stresses (Abe, 2002;Agarwal et al, 2006;Yang et al, 2018;Zhao, 2019). Dai et al (2012) first reported that OsMYB2P-1, an R2R3-MYB transcription factor, is involved in the regulation of phosphate-starvation responses in rice.…”
Section: Overexpression Of Ntmyb12 Enhances Plant Resistance To Low Pmentioning
confidence: 99%
“…For example, in Solanum lycopersicum Lefsm1, a SANT/MYB1-like1 protein seems to be involved in the early stage of fruit and plant development [66]. In A. thaliana, another SANT/MYB1 protein (RSM1) is involved in the apical hook formation [67], acts as a positive regulator of the sensitivity of ABA signaling during seed germination, and regulates the salinity levels [68]. These functions are also conserved in monocot species, such as O. sativa [69].…”
Section: Roles and Interactions Of DIV Drif And Radmentioning
confidence: 99%